SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN TINGKAT KUALITAS FISIK ATLET BOLA BASKET DENGAN MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCCES PADA PENGCAB PERBASI KABUPATEN SERANG - Waliadi Gunawan; Rizki Fatullah; Rio Mulyawan (Jurnal Ilmiah Sains dan Teknologi, 2019)
The Advances in technology future is growing very rapidly. This can be evidenced by the many innovations that simple, to the modern. Advances in technology are very important for human life, because the technology is one of the supporters of human progress. The method used in this research is a field research, literature and methods Analytic Hierarchy Process (AHP) which starts with collecting information, data relating to the Decision Support System To Determine Physical Quality and difference between one object to another object in order to obtain a maximum object after it is analyzed to find the problems and shortcomings in the Athlete Selection. These results indicate that the selection of physical Selection basketball athletes often discrepancies with the final result VO2max calculation formula and other formulas and the data is still not computerized so that the other party is still disa recognize these athletes their athletes. The Aims of this research is to develop a system that is still calculations manually into calculation used the Decision Support System (DSS) to determine the physical quality of basketball athletes on the basketball union branch managers throughout Indonesia (PERBASI) district for the performance of the coach / selectors can get a quality athlete. We make this decision support system can cope with the many incompatibilities and data loss can be overcome Athletes. With this system is implemented into a Sport Organization, the determination of the Calculation formula of VO2max and other formulas can be done quickly and accurately.